2018
DOI: 10.1098/rsos.172232
|View full text |Cite
|
Sign up to set email alerts
|

Response of Prochilodus nigricans to flood pulse variation in the central Amazon

Abstract: The influence of the flood pulse on fish populations has been posited, but infrequently tested or quantified. Here, we tested the effect of habitat on population size, using Prochilodus nigricans as a case study species. Floodplain habitat was based on the littoral zone area occupied by P. nigricans to feed. The magnitude of this habitat in each hydrological year, the moving littoral (ML), was expressed as the sum of daily littoral areas during the advancing flood pulse, using satellite-based passive microwave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
1
19
0
2
Order By: Relevance
“…The aquatic systems of the Baixada Maranhense are mainly regulated by the rains that occur in the region, and in such environments, in certain months of the year, there is a decrease in river flow, drastically modifying the environments, characterizing the so-called dry season (Gonçalves, 2005). Bayley et al (2018) studying biological, ecosystem and fishery data for Prochilodus nigricans in the central Amazon reports that the abundance of P. nigricans at the age of two was positively related to the breadth of the coastal zone and indicated that the population can be regulated by dependence density in relation to their main feeding habitat. Castello et al, (2019) analyzing the effect of floods on the abundance of fish of the species Colossoma macropomum describes that these flood patterns can influence food and development stages, since the availability of food and habitat are determined by interactions between flood events, availability of nutrients, cycling and biotic production processes, since these environments due to their dynamics are areas that present a high biological production and are widely exploited by fish from main channels and lakes.…”
Section: Introductionmentioning
confidence: 99%
“…The aquatic systems of the Baixada Maranhense are mainly regulated by the rains that occur in the region, and in such environments, in certain months of the year, there is a decrease in river flow, drastically modifying the environments, characterizing the so-called dry season (Gonçalves, 2005). Bayley et al (2018) studying biological, ecosystem and fishery data for Prochilodus nigricans in the central Amazon reports that the abundance of P. nigricans at the age of two was positively related to the breadth of the coastal zone and indicated that the population can be regulated by dependence density in relation to their main feeding habitat. Castello et al, (2019) analyzing the effect of floods on the abundance of fish of the species Colossoma macropomum describes that these flood patterns can influence food and development stages, since the availability of food and habitat are determined by interactions between flood events, availability of nutrients, cycling and biotic production processes, since these environments due to their dynamics are areas that present a high biological production and are widely exploited by fish from main channels and lakes.…”
Section: Introductionmentioning
confidence: 99%
“…Floodplain inundation greatly increases the area of available aquatic habitat and can provide access to abundant terrestrial and aquatic prey and other food sources, such as fruit and epiphytic algae (Correa, Costa‐Pereira, Fleming, Goulding, & Anderson, ; Douglas, Bunn, & Davies, ; Winemiller & Jepsen, ). The dynamism of habitat and food availability across the flood cycle strongly influences food web structure and ecosystem productivity on floodplains (Bayley, Castello, Batista, & Fabré, ; Warfe et al, ; Winemiller, ) and creates complex spatial patterns of species distribution and primary productivity (Pettit et al, ; Tonolla, Wolter, Ruhtz, & Tockner, ). The periodicity of floodplain inundation may also vary greatly among climatic regions, ranging from highly predictable, seasonal floods to unpredictable, arrhythmic events driven by stochastic climatic factors (Jardine et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Prochilodus nigricans Spix et Agassiz, 1829, locally known as curimatã, is very abundant and widespread in the Amazon Basin. Its adult population size is strongly correlated with floodplain habitats (Bayley et al 2018), feeding on detritus composed of fine organic particulates and algae. Prochilodus nigricans is a migratory species and large schools of this fish migrate to spawn at the floodplains adjacent to Amazonian large rivers (Araújo-Lima et al 2003, Granado-Lorencio et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…The presently reported study found a lack of fishing pressure on the younger age groups but with the caveat that the available data do not permit a complete stock assessment. And Bayley et al (2018) studied the relation between P. nigricans abundance and the flood pulse.…”
Section: Introductionmentioning
confidence: 99%